How important is the 'quality' of the cytotoxic T lymphocyte (CTL) response in protection against HIV infection? - Rowland-Jones, S; Pinheiro, S; Kaul, R; Hansasuta, P; Gillespie, G; Dong, T; Plummer, F; Bwayo, J; Fidler, S; Weber, J; McMichael, A; Appay, V (2001)
Cytotoxic T lymphocyte (CTL) responses have been associated with protection from HIV-1 infection in people with a high degree of exposure to HIV and who show no serological evidence of HIV infection (HEPS, highly exposed persistently seronegative). However, it remains unclear how protective CTL responses could apparently develop in a minority of people, whilst the great majority of HIV-infected people make strong CTL responses yet progress to AIDS and death. In this paper we review the data which supports the hypothesis that the quality of the T-cell response, rather than its magnitude, may be an important factor that merits further investigation.